Pengaruh Penerapan E-Procurement dan Sistem Pengendalian Internal Pemerintah Terhadap Pencegahan Kecurangan Pengadaan Barang dan Jasa Di Sektor Publik - Primastiwi, Anita; Wardani, Dewi Kusuma; Hanisah, Hanisah (LPPM Universitas Mataram, 2020)
This study aims to examine whether e-procurement, Whistleblowing System and internal control systems influence the prevention of fraudulent procurement of goods and services. This research method uses quantitative methods and primary data. The sample used in this study amounted to 63 respondents, namely employees of procurement of goods and services who have served at least 1 year in the environment of Yogyakarta City regional government agencies, the Procurement Services Unit and the Yogyakarta City Regional Work Unit. The sample method used was purposive sampling, while the data analysis technique used partial test. The results of research conducted indicate that the existence of e-procurement and internal control systems has a significant positive effect on fraud prevention of goods and services procurement